Isolation and characterization of bacteria from cooking utensil at UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah / Muhammad Aliff Zamri - Zamri, Muhammad Aliff (2018)
Bacteria is living things that can be found everywhere around us, including on the cooking utensil that are used for preparation of food. Usually this existence of bacteria on cooking utensil may due to poor level of cleanliness of the food handlers itself. The colonization of bacteria on cooking utensils may act as fomite for cross contamination of bacteria into food and may cause several implication to human health. A study was conducted in order to isolate and characterized the bacteria that exist on the cooking utensil. This study was conducted at two cafeteria in UiTM Cawangan Negeri Sembilan Kampus Kuala Pilah. The samples of bacteria colonies were collected by swabbing the cooking utensil surface and the sample were characterized by Gram staining reaction and several biochemical test. The biochemical test that were used to characterized the isolated bacteria are catalase, coagulase, indole, methyl red, Voges-Proskauer, citrate utilization test, motility test, triple sugar ion test and carbohydrate fermentation test. There are ten single colonies of bacteria isolated from this study. Six of bacteria colonies can be identified its genus while the other four are unidentified. The bacteria that were successfully isolated in this research are Staphylococcus spp. and Bacillus spp..